Integral sliding mode control design for high speed tilting trains - Zamzuri, Hairi (United Kingdom Simulation Society, 2010)

(untitled)
Active tilt technology has been widely used in high-speed railway vehicle. The used of ‘precedence’ tilt control design have been accepted most manufacture around the world. This technology has it on drawback due to the complexity and the control design parameter is depending on train velocity and track route to achieve satisfactory ride quality. This research is the extension work on investigating the local loop control scheme whereby the sensor not depending on vehicle in front, which reduce the complexity of control design. A proposed integral sliding mode control strategies aim to improved body roll responses in curved track while reducing the effect of straight track irregularities.